Object oriented simulation and optimization of hydrolectric power systems - Latorre Canteli, Jesús María; Cerisola Lopez De Haro, Santiago; Ramos Galán, Andrés (My University, 2016)
In this paper we present two models to evaluate the hydro scheduling of a multireservoir system. A simulation model based on the object oriented programming paradigm and another multi-objective optimization problem based on traditional mathematical programming tools are described. Both models are evaluated with real sized hydro basins elaborated from the Spanish hydrological system and comparisons between their results are given.

In this paper we present two models to evaluate the hydro scheduling of a multireservoir system. A simulation model based on the object oriented programming paradigm and another multi-objective optimization problem based on traditional mathematical programming tools are described. Both models are evaluated with real sized hydro basins elaborated from the Spanish hydrological system and comparisons between their results are given.